NA

Rút gọn biểu thức 

C=(1/x(x-1) +1/x(x+1)) . x2-1/x 

Với x khác 0 và x khác +-1

NH
26 tháng 12 2017 lúc 21:08

C = \(\left[\frac{1}{x}\left(x-1\right)+\frac{1}{x}\left(x+1\right)\right].x^2-\frac{1}{x}\)

 = \(\left[\frac{1}{x}.\left(x-1+x+1\right)\right].x^2-\frac{1}{x}\)

\(\frac{1}{x}.2x.x^2-\frac{1}{x}\)

\(2x^2-\frac{1}{x}\)

\(\frac{2x^3}{x}-\frac{1}{x}=\frac{2x^3-1}{x}\)

Bình luận (0)

Các câu hỏi tương tự
38
Xem chi tiết
NN
Xem chi tiết
NM
Xem chi tiết
LP
Xem chi tiết
VL
Xem chi tiết
PD
Xem chi tiết
MH
Xem chi tiết
HT
Xem chi tiết
CN
Xem chi tiết